Pengolahan Sampah Rumah Tangga Menjadi Kompos Di Kelurahan Labuh Baru Timur Pekanbaru - Latifa Siswati; Ambar Tri Ratna Ningsih; Jeniwardi Jeniwardi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Labuh Baru Timur Village already has a Waste Bank, but to process organic waste into compost, cadres of Waste Banks every RW still do not have that knowledge. The Unilak Community Service Team has the required knowledge, and through this activity knowledge transfer is carried out, so that the Waste Bank Cadre will be more optimal in managing the waste that has been collected in the Waste Bank of each RW. The method of activities given to the community is awareness, counseling, demonstration, and evaluation. Awareness is intended to give awareness to Waste Bank Cadres that managing waste into compost will have a positive impact on their environment. Counseling aims to provide knowledge to the community so that they are more sensitive to their environment so that the environment will provide beneficial results for their families. The demonstration aims to provide knowledge directly, both through picture shows, and the practice of directly composting household waste. And evaluation is carried out to determine the level of knowledge of partners before and after the activity, and to determine the success of the activity. The results of the activities concluded that the participants' knowledge, understanding, and skills could increase ranging from 4% -95%. And the composting speed depends on the size of the organic material used as the compost material, the smaller the size of the pieces of organic material, the faster the composting process will be. Bio activators used to play a role in accelerating the composting process, besides the homogeneity of materials is also a consideration in composting